THE CONSIDERATION FACTORS OF WHEEL LOADER PROVISION PROCESS FOR A CONSTRUCTION PROJECT - Mahmuddin, Mahmuddin -; Mubarak, Mubarak; Reja Pahlevie, Ricky (JURNAL TEKNIK SIPIL, 2022)
Abstract: The completion of a construction project is determined by various factors. One of these factors is related to the adequate availability of equipment resources both in terms of quantity, type, and function. The process for construction heavy equipment provision is generally carried out through the process of purchasing, renting or leasing. The factors that are considered in the supply of equipment are one of the problems that need to be studied further so that the target of effective project implementation can be achieved. Based on these problems, this study was conducted to identify the factors that are considered by contractors in the process of providing equipment in a construction project. This research is focused on the supply of wheel loader heavy equipment by a contractor company in Banda Aceh City. Data collection was carried out using a questionnaire as a research instrument, and involved the participation of 36 contractors with Medium (M1 and M2) and Large (B1) qualifications. The questionnaire instrument is structured into 6 factors consisting of cost, operation and maintenance factors, heavy equipment investment value, risk, equipment specifications and project conditions, and strategy. The process of data analysis applies descriptive statistical methods. The results of the analysis of the contractor's perception data indicate that the strategic factor is the most considered factor by the contractor in the provision of wheel loader heavy equipment. This condition is known from the indication of the average score of 3.11 as the highest value compared to other factors. The strategic factor becomes a top priority for contracting companies in supporting the improvement of the company's image or bona fide, especially when the company offers its services to the construction owner through a tender process.Keywords: provision, heavy equipment, wheel loader, construction project, Banda Aceh City